More Precise Values of Separation Factors in Water-Hydrogen Isotopic Exchange for Modeling of Combined Electrolysis and Catalytic Exchange Process. (3rd April 2017) - Ovcharov, A. V.
Abstract: Separation factors for ideal gas phase isotopic exchange reactions between water vapor and hydrogen were calculated for deuterium-protium exchange in the presence of trace amounts of tritium using adiabatic correction factors calculated by Bardo and Wolfsberg. The results obtained support the conclusions made by Bardo and later by Rolston that the application of adiabatic correction factors leads to slightly lower and more precise values of equilibrium constants or separation factors in comparison to separation factors straightforwardly calculated from the isotopic partition function ratios published by Bron, Chang and Wolfsberg. The difference for protium-trace tritium exchange is relatively low, at 333 K it amounts to 2.2%. Comparison with published experimental data on tritium exchange in the low deuterium concentration limit shows that the corrected values better reproduce experiment at least at temperatures below 383 K confirming earlier conclusions made for protium-deuterium exchange. Results are given in the form of 2D polynomial fits over wide range of deuterium concentration and temperature that is useful for the application of them in equation-oriented process modeling systems for the modeling of CECE process.